Soil testing and nutrient application practices of agricultural retailers in the Great Lakes Region - Sisung, Theresa (Kansas State University, 2016)
Agricultural runoff containing phosphorus is believed to be a major contributor of algae blooms in the Western Lake Erie Basin. However, the implementation of best management practices (BMPs) can be used to help reduce the runoff of phosphorus. This research involved conducting surveys to analyze the current implementation of BMPs in Michigan and Indiana. The hypothesis is that the survey results are similar between the two states. An additional hypothesis is that the Michigan and Indiana results are similar to results from two other studies that were previously conducted. The results from this research generally support the hypothesis that a similar number of farmers in Michigan and Indiana are already implementing best management practices on their farms. In addition to the results being similar across Michigan and Indiana, there is also some evidence that shows that the results are similar to studies from the Ohio State University (LaBarge and Prochaska 2014), CropLife magazine (Erickson and Widmar 2015) and NRCS (U.S. Department of Agriculture, Natural Resources Conservation Service 2016); however upon further investigation there are distinct differences before and after media mentions of ramifications from the Lake Erie algal blooms. While it is difficult to force farmers to implement BMPs, the results of this study may help to educate them, which may cause them to add these practices to their operations.
Keywords: Best management practices; Precision agriculture; Great Lakes; Soil testing; Nutrient application; Lake Erie